Preparation method and application of Co6W6C-POMOF-based bimetallic carbide composite electrocatalyst
By encapsulating tungsten-based POM in ZIFs pores and preparing Co6W6C-POMOF-based catalysts, the problem of structural instability of tungsten carbide-based catalysts during high-temperature synthesis is solved, and the activity and stability of efficient electrolyzing hydrogen production is achieved, replacing platinum base catalyst and reduce costs.
Patent Information
- Application Number
- CN202210870282.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-07-22
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2042-07-22
AI Technical Summary
Tungsten carbide-based catalysts are prone to overgrowth of crystals and collapse of pore structures during high temperature synthesis, resulting in low nanoification and insufficient exposure of active centers. The W-H bond energy in its electronic structure is too strong, which inhibits the desorption of hydrogen. , reducing its intrinsic hydrogen evolution activity.
Using the MOF space domain restriction strategy, tungsten-based POM is encapsulated into the ZIFs pores, and the Co6W6C-POMOF-based bimetallic carbide composite electrocatalyst is prepared through solvothermal reaction and heat treatment, to regulate its nanostructure and electronic structure, improve catalytic activity and stability sex.
In alkaline conditions and simulated seawater solutions, the Co6W6C-POMOF-based catalyst exhibits extremely high electrocatalytic hydrogen production activity and stability, which can replace the widely used platinum-based catalysts at present, reduce the cost of the catalyst and improve economic benefits .
Smart Images

Figure CN115295811B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of inorganic nanomaterials, and specifically relates to a preparation method and application of a Co6W6C-POMOF-based bimetallic carbide composite electrocatalyst. Background Art
[0002] Tungsten carbide is considered to be a favorable alternative to Pt-based catalysts due to its Pt-like electronic structure and can be widely used in water electrolysis hydrogen production half reaction (HER). Wirth et al.'s study on the acidic medium performance of IVB-VIB transition metal carbides in 2012 pointed out that tungsten carbide has the best catalytic activity, even better than the commercial MoxC that has been used in the hydrogen production end of the commercial all-aluminum redox flow battery and water electrolysis combined hydrogen production device, and has important commercial value.
[0003] However, there are currently two major difficulties in the research and application of tungsten carbide-based catalysts: (1) Traditional synthesis methods rely on high temperatures. The synthesis of tungsten carbide usually requires temperatures above 1000K, which can easily cause excessive crystal growth, resulting in a low degree of nano-sizing of the active center of the material and collapse of the pore structure, making it difficult to construct the microstructure of tungsten carbide; (2) The d-space density of the electronic structure of tungsten carbide is large, and the WH bond energy is too strong during the electrochemical process. H adsorbed on the surface of the material ads It is difficult to desorb to form hydrogen, which inhibits the intrinsic hydrogen evolution activity of tungsten carbide. The above research and application bottlenecks seriously restrict the exposure of active sites of tungsten carbide catalysts in the process of hydrogen production by electrolysis of water and the adsorption and desorption kinetics of reactants. Therefore, it is of great significance to develop new preparation methods to improve the intrinsic hydrogen evolution activity of tungsten carbide while stabilizing its nanostructure (including micromorphology, pore structure, etc.). Summary of the invention
[0004] In view of the above problems, the purpose of the present invention is to provide a MOF spatial confinement strategy to stabilize and regulate the bimetallic carbide Co6W6C electrocatalyst for efficient water electrolysis to produce hydrogen. The catalyst prepared in this way shows extremely high electrocatalytic hydrogen production activity and stability under alkaline conditions and simulated seawater solution, and can replace the platinum-based catalysts that are widely used at this stage.
[0005] Specifically, in a first aspect, the present invention provides a method for preparing a Co6W6C-POMOF-based bimetallic carbide composite electrocatalyst, comprising:
[0006] The zeolite imidazolate framework material ZIFs precursor is mixed with dimethylimidazole to obtain a confined template ZIFs; the confined template ZIFs powder is dispersed in an alcohol solution, and a tungsten source is added to obtain a mixed solution; the mixed solution is subjected to a solvothermal reaction to obtain a POMOF precursor; the POMOF precursor powder is heat-treated to obtain the Co6W6C-POMOF-based bimetallic carbide composite material electrocatalyst.
[0007] Preferably, the ZIFs precursor is cobalt nitrate hexahydrate Co(NO3)2·6H2O.
[0008] Preferably, the molar ratio of the ZIFs precursor to dimethylimidazole is 6-18:35-50.
[0009] Preferably, the tungsten source is tungsten hexachloride WCl6, sodium tungstate Na2WO4·xH2O, phosphotungstic acid H3O 40 PW 12 xH2O, tungstate H2WO4 and ammonium metatungstate (NH4)6H2W 12 O 40 At least one of the above, preferably phosphotungstic acid.
[0010] Preferably, the ratio of the confined template ZIFs powder to the tungsten source in the mixed solution is 50-200 mg: 0.05-0.3 mmol.
[0011] Preferably, the solvent thermal reaction conditions are: reaction at 110° C. for 3-8 hours.
[0012] Preferably, the heat treatment atmosphere is an inert atmosphere, preferably a nitrogen or argon atmosphere; the heat treatment temperature is 550-850° C., and the time is 2-5 hours.
[0013] In a second aspect, the present invention provides a Co6W6C-POMOF-based bimetallic carbide composite electrocatalyst obtained according to the above preparation method.
[0014] In a third aspect, the present invention provides an application of the above-mentioned Co6W6C-POMOF-based bimetallic carbide composite electrocatalyst in electrolytic catalytic hydrogen production in alkaline solution or simulated seawater solution.
[0015] Beneficial Effects
[0016] The present invention uses the "space confinement method" to encapsulate tungsten-based POM into the ZIFs pores, and successfully prepares the Co6W6C-POMOF-based bimetallic carbide composite electrocatalyst. This electrocatalyst can still retain its original nanostructure during the high-temperature carbonization process, which has great advantages over previous preparation methods.
[0017] The Co6W6C-POMOF-based bimetallic carbide composite electrocatalyst prepared by the present invention utilizes the electronic structure modulation effect between the cobalt source in the confined material ZIFs and the tungsten source encapsulated in the ZIFs to greatly reduce the overpotential of the catalyst in the hydrogen production reaction of water electrolysis in an alkaline solution, thereby greatly improving the hydrogen production activity and stability of the electrocatalyst. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 XRD patterns of the catalysts prepared in Example 1, Example 2, and Example 3;
[0019] Figure 2 These are electron microscope images of the catalyst prepared in Example 1, where a and b are SEM images, c is a TEM image and element distribution map, and d is a high-resolution TEM image;
[0020] Figure 3 HER catalytic performance curve of the catalyst prepared in the present invention in 1M KOH solution, wherein a is the linear sweep voltammetry curve (LSV curve) of the catalyst prepared in Examples 1-3, Comparative Examples 1-2 and a commercial 20wt.% Pt / C catalyst, and b is a stability test characterization diagram of the catalyst prepared in Example 1;
[0021] Figure 4 HER catalytic performance curves of the catalyst prepared in the present invention in a simulated seawater solution (3M NaCl+3M KOH), wherein a is the linear sweep voltammetry curve (LSV curve) of the catalyst prepared in Example 1 at different temperatures, b, c, d are the linear sweep voltammetry curves (LSV curves) of the catalyst prepared in Examples 1-3 in a simulated seawater solution (3M NaCl+3MKOH) at 30°C, 50°C, and 70°C, respectively, and e is a stability test curve of the catalyst prepared in Example 1 at different temperatures;
[0022] Figure 5 These are electron microscope images of the catalyst prepared in Example 2, where a is a SEM image and b is a TEM image;
[0023] Figure 6 These are electron microscope images of the catalyst prepared in Example 3, where a is a SEM image and b is a TEM image;
[0024] Figure 7 Phase characterization diagram of the material prepared in Comparative Example 1, where a is an XRD image and b is a SEM image;
[0025] Figure 8 Phase characterization diagram of the material prepared in Comparative Example 2, where a is an XRD image and b is a SEM image;
[0026] Fig. 9Phase characterization and catalytic performance diagram of materials prepared in Example 2, Comparative Example 3 and Comparative Example 4, wherein a is an XRD picture and b is a linear sweep voltammetry curve (LSV curve) of the material in 1 M KOH solution. DETAILED DESCRIPTION
[0027] The present invention is further described below by way of embodiments. It should be understood that the following embodiments are only used to illustrate the present invention, but not to limit the present invention.
[0028] In order to overcome the shortcomings of low HER catalytic efficiency, few active sites and poor micro-mesostructure of tungsten carbide-based catalysts, and to achieve the design and preparation of non-precious metal HER catalysts with better catalytic activity and stability than platinum-based catalysts, the present invention provides a preparation method using a "spatial confinement strategy", which simultaneously achieves the regulation of the morphology and structure of tungsten carbide and the optimization of the electronic structure brought about by heterogeneous element doping, and obtains a Co6W6C-POMOF-based bimetallic carbide composite electrocatalyst.
[0029] Among them, MOF-based materials have rich multi-level pore structures and nanocavity structures that can accommodate catalytic guests, and can confine and carbonize catalytic guests of suitable size, thereby realizing the regulation and stabilization of the morphology of catalytic materials. POM-based materials are d-zone transition metal oxide clusters (such as W, Mo, etc.) with high oxidation states, and metal complexes with oxygen-containing ligands. The size of the complex is extremely small, and it can enter the nanocavity of the MOF base through material design to achieve the coordination of POM@MOF and the spatial confinement effect of MOF. Based on this, the present invention selects ZIF-67 (a structure of MOF) as the main body, and in situ captures POM-W (~1nm) through its rich Co element and suitable nanocavity size (>1nm), and realizes the regulation of the morphology of tungsten carbide and the optimization of the electronic structure brought by heterogeneous element doping through co-carbonization. The electrocatalyst provided by the present invention can be widely used in electrolysis and hydrogen production in alkaline solutions and simulated seawater solutions.
[0030] The POMOF-based bimetallic carbide composite electrocatalyst provided by the present invention not only overcomes the negative effects of traditional high temperature such as grain growth, morphology collapse and pore structure destruction, but also introduces heterogeneous transition metals to modulate the WC electronic structure, which not only improves the strong WH bond effect of the tungsten carbide-based catalyst to the greatest extent, optimizes the hydrogen adsorption effect in the HER reaction, and improves the intrinsic hydrogen evolution activity of the tungsten carbide-based material; at the same time, by utilizing the spatial confinement effect of ZIF, POMs are successfully encapsulated into the ZIFs pores to stabilize their original morphology during the high-temperature carbonization process, successfully constructs a micro-mesoscopic nanostructure to expose the active sites to the greatest extent, greatly increases the catalytic performance of the tungsten carbide-based catalyst, reduces the catalyst cost, and has high economic benefits and practical value.
[0031] The following is an exemplary description of the preparation method of the Co6W6C-POMOF-based bimetallic carbide composite electrocatalyst of the present invention, and the preparation method mainly includes the following steps.
[0032] (1) Preparation of confined template ZIFs: 6-18 mmol of zeolite imidazolate framework material ZIFs precursor and 35-50 mmol of dimethylimidazole are uniformly mixed in an alcohol solution (such as methanol), and reacted at room temperature for 2-4 hours; then, the product is centrifuged, washed, and dried to obtain the confined template zeolite imidazolate framework material ZIFs.
[0033] In some embodiments, the ZIFs precursor may be cobalt nitrate hexahydrate (Co(NO3)2·6H2O). The Co element in cobalt nitrate hexahydrate can achieve Co doping while limiting material growth.
[0034] (2) Preparation of POMOF precursor powder. Take 50-200 mg of the confined template ZIFs powder prepared in step (1), disperse it in a 30-50°C methanol solution for 10-20 hours to fully open the ZIFs pore structure; then, add 0.05-0.3 mmol of tungsten source to the ZIFs methanol solution dispersed with the fully opened pore structure, react for 20-40 minutes, and obtain a uniformly dispersed mixed solution; then, transfer the above-mentioned uniformly dispersed mixed solution to a hydrothermal reactor, and perform a solvent thermal reaction at 110°C for 3-8 hours to allow the tungsten source to enter the ZIFs pore structure; the product is centrifuged, washed, and vacuum dried to obtain the POMOF precursor powder.
[0035] In some embodiments, the tungsten source may be tungsten hexachloride (WCl6), sodium tungstate (Na2WO4·xH2O), phosphotungstic acid (H3O 40 PW 12 ·xH2O), tungstic acid (H2WO4) and ammonium metatungstate ((NH4)6H2W 12 O 40 ) at least one; preferably phosphotungstic acid, because its group size is compatible with ZIFs (~1nm), it can ensure its successful encapsulation into the nanocavity structure of ZIFs (>1nm), thereby ensuring the realization of the subsequent encapsulation carbonization process.
[0036] (3) In-situ encapsulation carbonization: The POMOF precursor powder prepared in step (2) is placed in a tube furnace for heat treatment to obtain the Co6W6C-POMOF-based bimetallic carbide composite material nano-electrocatalyst of uniform size.
[0037] The heat treatment atmosphere is an inert atmosphere, preferably a nitrogen or argon atmosphere; the heat treatment temperature is 550-850°C, and the time is 2-5 hours. The in-situ encapsulation carbonization of the material is achieved by heat treatment. If the heat treatment temperature is too low, the material cannot be crystallized, and the activity of the prepared catalyst is too low; if the heat treatment temperature is too high, the encapsulated carbonized bimetallic carbide nanoparticles are prone to grain growth and tungsten carbide phase segregation, which also affects the catalytic activity of the catalyst material HER.
[0038] As a preparation scheme for Co6W6C-POMOF based bimetallic carbide composite electrocatalyst, the following steps can be adopted:
[0039] (1) 6-18 mmol of cobalt nitrate hexahydrate and 35-50 mmol of dimethylimidazole are uniformly mixed and reacted at room temperature for 2-4 hours. The product is centrifuged, washed, and vacuum dried to obtain encapsulated confined template ZIFs;
[0040] (2) dispersing 50-200 mg of the ZIFs powder obtained in step (1) in a methanol solution at 30-50° C. for 10-20 h, then adding 0.05-0.3 mmol of tungsten source and reacting for 20-40 min;
[0041] (3) transferring the uniformly dispersed mixed solution in step (2) to a hydrothermal reactor, hydrothermally heating at 110° C. for 3 to 8 h, and then centrifuging, washing, and vacuum drying to obtain a POMOF precursor powder;
[0042] (4) The POMOF powder obtained in step (3) is heat treated in an inert atmosphere for 2 to 5 hours at a temperature of 550 to 850° C. to obtain a Co6W6C-POMOF-based bimetallic carbide composite electrocatalyst.
[0043] The present invention adopts the "cage confinement method" and utilizes ZIFs with rich pore structures and nanocavity structures that can accommodate catalytic guests to simultaneously achieve morphology control and electronic structure optimization of tungsten carbide, and prepare non-precious metal bimetallic carbide Co6W6C doped with heterogeneous elements for efficient water electrolysis and hydrogen production (HER). Among them, the heterogeneous metal elements provided by the confined template are in close contact with the tungsten source inside the template pores, and co-carbonization is achieved at high temperatures. The heterogeneous metal elements optimize the electronic structure of tungsten carbide, and the confinement effect of the confined template stabilizes the micro-mesoscopic morphology of tungsten carbide during the high-temperature carbonization process, so that the prepared electrocatalyst exhibits excellent HER catalytic activity.
[0044] The Co6W6C nanomaterial prepared by the present invention presents a regular dodecahedron structure with a wrinkled surface, a particle size of about 500nm, and a specific surface area of 10-100m 2 / g, with a rich pore structure, in which Co and W elements are co-carbonized and evenly distributed. The surface of the regular dodecahedron material is wrapped with a carbon layer, which, on the one hand, improves the conductivity of the material and promotes the rapid transmission of electrons in the catalytic reaction; on the other hand, it ensures the catalytic stability of the Co6W6C active site in the long-term HER reaction.
[0045] In the present invention, the precursor containing the W element is confined inside the MOF cavity containing the Co element. During the high-temperature carbonization process, due to the limitation of the MOF cavity, the tungsten carbide is successfully doped with the late transition metal Co while retaining a uniform size and morphology, thereby realizing Co modulation of the electronic structure of W, optimizing the d-band electronic state density of W, weakening the WH bond energy, improving the rapid desorption of Hads, accelerating the HER catalytic process, and greatly improving the HER catalytic efficiency, and finally obtaining a Co6W6C bimetallic carbide catalytic material with good HER catalytic performance and stability.
[0046] The Co6W6C-POMOF-based bimetallic carbide composite electrocatalyst disclosed in the present invention can be applied to electrolytic catalytic hydrogen production in alkaline and simulated seawater environments. It exhibits excellent hydrogen evolution catalytic activity in both 1M KOH alkaline solution and 3M NaCl+3M KOH simulated seawater solution, with a current density of 10mA / cm 2 The overpotentials at 50mV and 47mV are respectively. At the same time, the catalytic material also has high catalytic stability, can maintain good hydrogen evolution catalytic activity at room temperature, and also has good catalytic durability under simulated industrial high temperature.
[0047] The following examples are further cited to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention, and the specific process parameters of the following examples are only an example within the appropriate range.
[0048] Example 1
[0049] According to the above technical scheme and process flow of the present invention: 12mmol of cobalt nitrate hexahydrate and 48mmol of dimethylimidazole are added to 30mL of methanol solution, reacted at room temperature for 4h, centrifuged, washed and dried to obtain confined encapsulation template ZIFs.
[0050] 100 mg of ZIFs powder was dissolved in 30 mL of methanol solution, stirred at 30 °C for 12 h, and then 0.15 mmol of phosphotungstic acid was added and stirred for 30 min. Then, the mixed solution was transferred to a hydrothermal autoclave, hydroheated at 110 °C for 6 h, centrifuged, washed, and dried to obtain a POMOF precursor powder with the tungsten source encapsulated into ZIFs.
[0051] The POMOF precursor powder obtained above was placed in an argon atmosphere tubular furnace and heat treated at 600°C for 4 hours to obtain a Co6W6C-POMOF-based bimetallic carbide composite electrocatalyst, and the material was named POMOF-15-600.
[0052] Figure 1 This is the XRD pattern of the catalyst prepared in Example 1. It can be seen from the figure that the main phase of the catalyst prepared in Example 1 is Co6W6C.
[0053] Figure 2 The electron microscope images of the catalyst prepared in Example 1, a and b are SEM images, c is a TEM image and element distribution map, and d is a high-resolution TEM image. Figure 2 a, b) and TEM( Figure 2 c) As can be seen from the figure, the main morphology of the catalyst prepared in Example 1 is a regular dodecahedron with a wrinkled surface, which is about 500 nm in size; EDS shows that Co, W, C, and N are uniformly dispersed inside the catalyst prepared in Example 1, and no obvious aggregation occurs; from the high-resolution TEM ( Figure 2 As can be seen from Figure d), d = 0.21nm and d = 0.19nm, corresponding to the (511) and (440) crystal planes of Co6W6C, respectively.
[0054] Figure 3 The HER catalytic performance curve of the catalyst prepared in the present invention in 1M KOH solution is shown in Figure a, wherein a shows the linear sweep voltammetry curve (LSV curve) of the catalyst prepared in Example 1, and b is a stability test characterization diagram of the catalyst prepared in Example 1. Figure 3 As can be seen from (a), the catalyst prepared in Example 1 has a current density of 10 mA / cm in 1 M KOH alkaline electrolyte. 2 The overpotential of HER electrocatalysis is 50 mV; Figure 3 As can be seen from (b), the HER performance of the catalyst prepared in Example 1 can still be maintained after 10,000 cycles.
[0055] Figure 4 (a)-(d) are linear sweep voltammetry curves (LSV curves) of the catalyst prepared in Example 1 in simulated seawater solution (3M NaCl+3M KOH) at different temperatures; Figure 4 (e) is a stability test curve at different temperatures for the catalyst prepared in Example 1. It can be seen from the figure that the catalyst prepared in Example 1 also has good catalytic performance and catalytic stability in simulating industrial hydrogen production from seawater.
[0056] Example 2
[0057] The technical scheme and process flow refer to Example 1. The main difference is that the amount of phosphotungstic acid added is 0.05 mmol. The obtained material is named POMOF-5-600.
[0058] Figure 1 This is the XRD pattern of the catalyst prepared in Example 2. It can be seen from the figure that the main phase of the catalyst prepared in Example 2 is Co6W6C.
[0059] Figure 3 (a) is the HER catalytic LSV curve of the catalyst prepared in Example 2 in 1M KOH solution; Figure 4 (b)-(d) are the HER catalytic LSV curves of the catalyst prepared in Example 2 in simulated seawater solution (3M NaCl+3M KOH) at 30°C, 50°C, and 70°C, respectively. It can be seen from the figure that the HER activity of the catalyst prepared in Example 2 is slightly worse than that of Example 1.
[0060] Figure 5 The electron microscope pictures of the catalyst prepared in Example 2, wherein a is a SEM picture and b is a TEM picture. It can be seen from the figure that the morphology of the catalyst prepared in Example 2 is a regular dodecahedron structure with a wrinkled surface.
[0061] Example 3
[0062] The technical scheme and process flow refer to Example 1. The main difference is that the amount of phosphotungstic acid added is 0.25 mmol. The obtained material is named POMOF-25-600.
[0063] Figure 1 This is the XRD pattern of the catalyst prepared in Example 3. It can be seen from the figure that the main phase of the catalyst prepared in Example 2 is Co6W6C.
[0064] Figure 3 (a) is the HER catalytic LSV curve of the catalyst prepared in Example 3 in 1M KOH solution; Figure 4 (b)-(d) are the HER catalytic LSV curves of the catalyst prepared in Example 3 in simulated seawater solution (3M NaCl+3M KOH) at 30°C, 50°C, and 70°C, respectively. It can be seen from the figure that the HER activity of the catalyst prepared in Example 3 is slightly worse than that of Example 1.
[0065] Figure 6 The electron microscope pictures of the catalyst prepared in Example 3, wherein a is a SEM picture and b is a TEM picture. It can be seen from the figure that the morphology of the catalyst prepared in Example 3 is a regular dodecahedron structure with a wrinkled surface.
[0066] Comparative Example 1
[0067] The technical solution and process flow refer to Example 1. The main difference is that no tungsten source is added. The obtained material is named Co-NC.
[0068] Figure 7 The material phase characterization diagram of the material prepared in Comparative Example 1, wherein a is an XRD image and b is a SEM image. It can be seen from the figure that the obtained material phase is a mixed phase of metallic cobalt and cobalt oxide, and the morphology is a regular dodecahedron structure with a wrinkled surface.
[0069] Figure 3 (a) is the HER catalytic LSV curve of the catalyst prepared in Comparative Example 1 in 1M KOH solution. It can be seen from the figure that the material without adding tungsten precursor exhibits extremely poor HER catalytic activity.
[0070] Comparative Example 2
[0071] The technical solution and process flow refer to Example 1. The main difference is that the cobalt nitrate hexahydrate is replaced by zinc nitrate hexahydrate. The obtained material is named W-NC.
[0072] Figure 8 The phase characterization diagram of the material prepared in Comparative Example 2, where a is an XRD image and b is a SEM image. It can be seen from the figure that the morphology of the material prepared in Comparative Example 2 is irregular nanoparticles, indicating that the confinement template generated by zinc nitrate and dimethylimidazole does not match the size of the tungsten source, and there is no obvious confinement effect during the in-situ carbonization process.
[0073] Figure 3 (a) is the HER catalytic LSV curve of the catalyst prepared in Comparative Example 2 in 1M KOH solution. It can be seen from the figure that the material without adding cobalt element exhibits extremely poor HER catalytic activity.
[0074] Comparative Example 3
[0075] The technical solution and process flow refer to Example 2. The main difference is that the heat treatment temperature is adjusted to 500° C. The obtained material is named POMOF-15-500.
[0076] Fig. 9 The phase characterization and catalytic performance diagram of the material prepared in Comparative Example 3, where a is the XRD picture and b is the LSV curve in 1M KOH solution. It can be seen from the figure that the material prepared in Comparative Example 3 is not crystallized and has almost no catalytic activity.
[0077] Comparative Example 4
[0078] The technical solution and process flow refer to Example 2. The main difference is that the heat treatment temperature is adjusted to 900° C. The obtained material is named POMOF-15-900.
[0079] Fig. 9 The phase characterization and catalytic performance diagram of the material prepared in Comparative Example 4, where a is the XRD picture and b is the LSV curve in 1M KOH solution. It can be seen from the figure that the material prepared in Comparative Example 4 has WC crystal phase segregation, and the catalytic activity is significantly attenuated compared with the material in Example 1.
[0080] Although the content of the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as a limitation of the present invention. After reading the above content, it will be apparent to those skilled in the art that various modifications and substitutions of the present invention will occur. Therefore, the protection scope of the present invention should be limited by the appended claims.
Claims
1. A method for preparing a Co6W6C-POMOF-based bimetallic carbide composite electrocatalyst, characterized in that: include: The precursor of zeolitic imidazolate framework material ZIFs is mixed with dimethylimidazole to obtain confined template ZIFs; The confined template ZIFs powder is dispersed in an alcohol solution, and a tungsten source is added to obtain a mixed solution; the mixed solution is subjected to a solvothermal reaction to obtain a POMOF precursor; the POMOF precursor powder is subjected to a heat treatment to obtain the Co6W6C-POMOF-based bimetallic carbide composite material electrocatalyst; The ZIFs precursor is cobalt nitrate hexahydrate Co(NO3)2·6H2O, and the tungsten source is tungsten hexachloride WCl6, sodium tungstate Na2WO4·xH2O, phosphotungstic acid H3O 40 PW 12 xH2O, tungstate H2WO4 and ammonium metatungstate (NH4)6H2W 12 O 40 At least one of; The heat treatment temperature is 550-850° C. and the time is 2-5 hours.
2. The preparation method according to claim 1, characterized in that: The molar ratio of the ZIFs precursor to dimethylimidazole is 6-18:35-50.
3. The preparation method according to claim 1, characterized in that The dosage ratio of the confined template ZIFs powder to the tungsten source in the mixed solution is 50-200 mg: 0.05-0.3 mmol.
4. The preparation method according to claim 1, characterized in that: The solvent thermal reaction conditions are: reaction at 110° C. for 3-8 hours.
5. The preparation method according to claim 1, characterized in that: The atmosphere of the heat treatment is an inert atmosphere.
6. The preparation method according to claim 5, characterized in that: The inert atmosphere is a nitrogen or argon atmosphere.
7. A Co6W6C-POMOF-based bimetallic carbide composite electrocatalyst obtained according to the preparation method of claim 1.
8. An application of the Co6W6C-POMOF-based bimetallic carbide composite electrocatalyst according to claim 7 in electrolytic catalytic hydrogen production in alkaline solution or simulated seawater solution.
Citation Information
Patent Citations
Oxygen evolution ferrocobalt-cobalt ferrite / nitrogen-doped nano-carbon tube composite catalyst and preparation method and application thereof
CN109524678A
Preparation method of multi-metal carbide electro-catalyst
CN111054411A